Protection Security Assessment - Fuzzification of Relay Settings for Weak Spot Detection - Dauer, Maximilian; Jäger, Johann; Bopp, Thomas; Krebs, Rainer (APAP Protection and Automation Conference, 2013)
This paper addresses the challenge of weak spot detection of a proposed protection scheme. The presented method analyzes the protection system of a power network and checks for limits of the setting methodology. The approach is useful for system-wide analysis. A fuzzy system was developed therefore. Fuzzificated values are computer-readable linguistic values. They can describe the system in a more detailed way, as an engineer would do. The use of a fuzzy system enables the possibility of integration in an automated application. This method is system-wide, knowledge-based and self-adaptive. To validate this benefit a comparison has been done between the fuzzy system and the commonly proofed method fingerprint analysis. The paper demonstrates the capability of the presented fuzzy system to detect weak spots of the protection system globally, to find the reason for this in a suboptimal methodology and to calculate these findings very fast. Index Terms-fingerprint analysis, fuzzy logic, power system reliability and security, power system planning, power system protection, protection security assessme